Frame Тheory as a Language of Conflict Description - Saghatelyan, Sona (Journal of Sociology: Bulletin of Yerevan University, 2015)
Topicality and methodological potential of analysis of conflict as a constructed social event from perspectives of constructivist methodology and cognitive sociology are argued. The connection between observation, differentiation and framing of conflict, aimed at outlining theoretical and methodological basics of frame analysis of conflict is considered.
Keywords: conflict image, event construction, framing, differentiation orders, meaning production, nomination, categorization, conflict of interpretation, observation systems, cognitive construct